2002
DOI: 10.1053/jhep.2002.36156
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive lamivudine therapy based on HBV DNA level in HBsAg-positive kidney allograft recipients

Abstract: Hepatitis B surface antigen (HBsAg)-positive kidney transplant recipients have increased liver-related mortality. The impact of lamivudine treatment on patient survival, the optimal time to start treatment, and the feasibility of discontinuing treatment have not been determined. This study examined these issues with a novel management protocol. Serum hepatitis B virus (HBV) DNA levels were measured serially in HBsAg-positive kidney transplant recipients, and lamivudine was administered preemptively to patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 42 publications
2
133
1
Order By: Relevance
“…None of the HBsAg positive patients receiving prophylactic or pre-emptive therapy developed reactivation, while 50% of the patients not been treated suffered reactivation [51,52] . These results were confirmed by others, but there is some controversy about the clinical impact of prophylactic/preemptive therapy vs salvage therapy [51][52][53][54][55] . One study showed that there was no differences in survival between HBsAg positive RT patients treated preemptively with LAM and HBsAg negative controls.…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 52%
See 1 more Smart Citation
“…None of the HBsAg positive patients receiving prophylactic or pre-emptive therapy developed reactivation, while 50% of the patients not been treated suffered reactivation [51,52] . These results were confirmed by others, but there is some controversy about the clinical impact of prophylactic/preemptive therapy vs salvage therapy [51][52][53][54][55] . One study showed that there was no differences in survival between HBsAg positive RT patients treated preemptively with LAM and HBsAg negative controls.…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 52%
“…One study showed that there was no differences in survival between HBsAg positive RT patients treated preemptively with LAM and HBsAg negative controls. HBsAg positive patients transplanted without preemptive therapy had in increased mortality rate [relative risk of death, 9.7 (P < 0.001); relative risk of liver-related mortality, 68.0 (P < 0.0001) [53] . Twenty five RT candidates received pre-transplantation prophylactic/preemptive NUC therapy, 22 (88%) were treated with LAM and 3 (12%) with ETV [54] .…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 99%
“…Based on previous report, the incidence of lamivudine resistance was ~14-32% after 1 year and ~60-70% after 5 years of therapy for patients with CHB (20). Despite its prophylactic use, drug-resistant mutations and hepatitis flares have been reported in patients treated with lamivudine during immunosuppressive therapy (18,30). Recently, a newer generation of oral antivirals with higher antiviral potency, such as entecavir and tenofovir, have become available.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with positive HBsAg, a higher HBV DNA level prior to therapy (>2,000 IU̸ml) has been demonstrated to be an important risk factor for HBV reactivation compared with those having lower HBV DNA levels (11,12 HBV DNA levels; however, the risk of HBV reactivation remains higher for the minority with detectable HBV DNA at baseline (13,14). To prevent HBV reactivation during cancer chemotherapy, clinical studies, including randomized controlled trials, demonstrated that prophylactic use of an oral antiviral agent, mainly lamivudine, may reduce the rate of HBV reactivation and the severity of associated hepatitis flares and mortality (15)(16)(17)(18)(19). According to the 2009 American Association for the Study of Liver Diseases (AASLD) CHB practice guideline update (20), patients with a high baseline HBV DNA (>2,000 IU̸ml) level must continue treatment until they reach treatment endpoints as in immunocompetent patients.…”
Section: Introductionmentioning
confidence: 99%
“…The primary goals of management are maximal suppression of viral replication, while minimizing development of resistance and prevention of hepatic fibrosis. Cessation of antiviral therapy in the immunocompromised host is associated with an increased risk of flare of liver disease and rarely decompensated liver disease in transplant recipients (Chan et al, 2002;Liaw et al, 1999). Indefinite therapy carries its own risks, including that of antiviral toxicity (rare) and of drug resistance.…”
Section: Timing Of Initiationmentioning
confidence: 99%